2011
DOI: 10.1038/hdy.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for sexually dimorphic fitness-related traits in wild bighorn sheep

Abstract: Dissecting the genetic architecture of fitness-related traits in wild populations is key to understanding evolution and the mechanisms maintaining adaptive genetic variation. We took advantage of a recently developed genetic linkage map and phenotypic information from wild pedigreed individuals from Ram Mountain, Alberta, Canada, to study the genetic architecture of ecologically important traits (horn volume, length, base circumference and body mass) in bighorn sheep. In addition to estimating sex-specific and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 67 publications
(90 reference statements)
2
61
3
Order By: Relevance
“…; Poissant et al . ), with some studies involving controlled crosses (Laporte et al . ) or breeding in captivity (Knief et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Poissant et al . ), with some studies involving controlled crosses (Laporte et al . ) or breeding in captivity (Knief et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Poissant et al . ), and others failing to detect candidate causal variants despite moderately high heritability (Santure et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, such effects have rarely been assessed in wild populations and natural habitats (Slate ; Poissant et al . ). In this study, significant GEI was found in four out of six individual loci (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…), a trait genetically correlated to female mass (genetic correlation = 0.43; Poissant et al. ). It was therefore suggested that anthropogenic pressures, such as selective hunting, could lead indirectly to maladaptive changes in female mass and potentially negatively affect population dynamics (Kuparinen and Festa‐Bianchet ).…”
Section: Discussionmentioning
confidence: 99%
“…From 1988 (except 1994 to 1996), tissue samples were collected for genetic analysis (Poissant et al. ). Paternities were assigned using CERVUS (Marshall et al.…”
Section: Methodsmentioning
confidence: 99%